1998
DOI: 10.1209/epl/i1998-00273-1
|View full text |Cite
|
Sign up to set email alerts
|

The dimer model for κ-phase organic superconductors

Abstract: We prove that the upper electronic bands of κ-phase BEDT-TTF salts are adequately modeled by an half-filled tight-binding lattice with one site per cell. The band parameters are derived from recent ab initio calculations, getting a very simple but extremely accurate one-electron picture. This picture allows us to solve the BCS gap equation adopting a real-space pairing potential. Comparison of the calculated superconducting properties with the experimental data points to isotropic s0-pairing. Residual many-bod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…References [59,127] and references therein for a review and discussion) to derive values λ ∼ 0.3. Similarly, infrared measurements [128] have been taken to suggest that "intramolecular vibrations are not directly involved in the superconductivity mechanism" and that the electron-phonon coupling constant is small; others found "no evidence that higher values of T c are achieved through a softer lattice" (i.e. that intermolecular vibrations are not involved in a simple, BCS-like manner) and that the superconductivity "is likely to be a much Normalised frequency of the…”
Section: Summary Of Optical Datamentioning
confidence: 99%
“…References [59,127] and references therein for a review and discussion) to derive values λ ∼ 0.3. Similarly, infrared measurements [128] have been taken to suggest that "intramolecular vibrations are not directly involved in the superconductivity mechanism" and that the electron-phonon coupling constant is small; others found "no evidence that higher values of T c are achieved through a softer lattice" (i.e. that intermolecular vibrations are not involved in a simple, BCS-like manner) and that the superconductivity "is likely to be a much Normalised frequency of the…”
Section: Summary Of Optical Datamentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] From the first-principles approach, Xu et al calculated the Fermi surfaces of -͑BEDT-TTF͒ 2 Cu͑NCS͒ 2 using the local density approximation ͑LDA͒ based on the density functional theory ͑DFT͒. 5 From the ab initio molecular orbital ͑MO͒ theory, Demiralp and Goddard optimized the BEDT-TTF monomer at HF/6-31G** and studied the physical properties using the 2-D Hubbard model within the Hartree-Fock ͑HF͒ approximation.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Fortunelli and Painelli described the ab initio evaluation of Hubbard parameters for the BEDT-TTF dimer unit of the -͑BEDT-TTF͒ 2 Cu͓N͑CN͒ 2 ͔Br salt. [14][15][16][17] Okuno and Fukutome showed an effective Hamiltonian of ␤-and -phases and concluded that the electron correlation is very strong. 18 The nesting and pressure effects of the Fermi surface were discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…1). Furthermore, it has been possible to fit experimental Fermi-surface-topology data to a simplified model of the tight-binding band structure (the so-called effective dimer model) to a good degree of accuracy [5,[9][10][11].The combination of unconventional superconductivity and a tractable analytical representation of the band structure makes the k-͑BEDT-TTF͒ 2 X superconductors attractive for theoretical studies, and a number of authors [9,10,12,13] have explored the possibility of d-wave superconductivity mediated by spin fluctuations. Such approaches predict that the superconducting order parameter will have four, roughly perpendicular, gap nodes, the exact orientation of the nodes depending on the underlying details of the Fermi surface [10,12].…”
mentioning
confidence: 99%